The Use of Field Spectroscopy for the Implementation of Vegetation Indices for the Satellite Remote Sensing Detection of Underground Military Structures in Cyprus - Melillos, George; Themistocleous, Kyriacos; Agapiou, Athos; Michaelides, Silas; Papadavid, George; Hadjimitsis, Diofantos G. (My University, 2020)
This paper aims to explore the integration of field spectroscopy and satellite remote sensing approaches to detect underground structures in Cyprus. A SVC-HR1024 field spectroradiometer was used and in-band reflectances were determined for medium resolution Landsat 7 ETM satellite sensor. In order to study possible differences of the spectral signature of vegetation, Normalized Difference Vegetation Index (NDVI), Simple Ratio (SR) and Enhanced Vegetation Index (EVI) have been used for the detection of underground military structures. The simulation results show that Vegetation Indices are highly useful and extremely valuable for detection underground infrastructures in Cyprus. In this study, two test areas were identified, analyzed and modelled: Area (a) which is a Vegetation Area covered with vegetation (barley), in the presence of an underground military structure, and Area (b) which is a Vegetation Area covered with vegetation (barley), in the absence of an underground military structure.
Keywords: Field spectroscopy; Remote sensing; Underground structures; Vegetation indices